Learner’s perception of task difficulties in technology-mediated task-based language teaching - Butarbutar, Ranta (Englisia: Journal of Language, Education, and Humanities, 2021)
The perception of learners can be used for evaluating task-based language teaching development. However, during the technology-mediated task-based language teaching (TBLT), learners faced a few difficulties. Thus, this study aimed to investigate learners’ perceptions of task difficulties in technology-mediated (TBLT). To collect data, the study used a quantitative design with an open-ended questionnaire, and, involved two hundred learners as participants who came from different departments at the university. The results strongly confirmed that incorporating technology into TBLT leads learners to face some difficulties in (1) understanding the meaning of the task, (2) practical instruction in doing tasks, (3) applying new technology to explore profound tasks further, (4) lack of direct lecturer feedback on student tasks, (5) performance assessment, (6) addressing learners’ needs, (7) goal orientation, (8) digital literacy, building knowledge, intellectual, and behavior, and (9) school and curriculum rules. Furthermore, the study preferred some strategies to solve learners' difficulties in TBLT, such as managing teaching materials to become easier and more interesting, referring technology integration to learners’ ability, implementing bring your own device (BYOD), improving classroom assessment, teachers broadening technology-mediated, task-based learning internships, and facilitating learners with compatible technology tools and stable internet connection.